Legal Responsibility for Autonomous Management of Chemicals in Japan - Handa, Arimichi; Nakahara, Hirohiko; Eguchi, Hisashi; Manabe, Noriyuki; Takebayashi, Toru; Takayama, Hiromitsu (Journal of Occupational Health Law, 2024)
The Order for Enforcement of Industrial Safety and Health Act and otherlaws and regulations are being revised with a view to a new method of chemicalsubstance management based on autonomous management. Based on theguidelines and manuals issued by the Ministry of Health, Labour and Welfareand other relevant ministries and agencies, companies and workplaces have beensearching for appropriate measures, incorporating exchanges of opinions amongcompanies and workplaces as needed. In this symposium, in light of the currentsituation, we deepened the discussion on the legal risks associated with theautonomous management of chemical substances that may arise in the future.